2023
DOI: 10.4236/as.2023.149089
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Effects of Selected Organic Fertilizer on Growth and Yields of Tomato (<i>Lycopersicon esculentum</i>: Var. Rio Grande Tomatoes) in Mundri West County, Western Equatoria State, South Sudan

Joseph Mayindo Mayele,
Felix Rufas Abu

Abstract: Worldwide, the demand for agro-organic foods that are healthy, nutritious, and environmentally friendly is increasing dramatically across all nations among consumers. Tomatoes being one of the dietary requirements in almost every meal is not exceptional and its availability in the market all year round is very important to farmers as well as consumers because it is highly demanded as a vegetable par excellence; which is either eaten raw in salads, cooked or processed into liquid ingredients. This study investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 54 publications
2
1
0
Order By: Relevance
“…Usman [62] observed a significant increase by poultry manure (20 t ha −1 ) on tomato plant height at 2, 4, 6 and 8 weeks after transplanting as compared to cattle and goat manure. Similar results were also reported by Mayele and Abu [63].…”
Section: Effect Of Tillage and Manure Rate On Aboveground Biomass Lai...supporting
confidence: 92%
See 2 more Smart Citations
“…Usman [62] observed a significant increase by poultry manure (20 t ha −1 ) on tomato plant height at 2, 4, 6 and 8 weeks after transplanting as compared to cattle and goat manure. Similar results were also reported by Mayele and Abu [63].…”
Section: Effect Of Tillage and Manure Rate On Aboveground Biomass Lai...supporting
confidence: 92%
“…The high sunflower yield means recorded in the second cropping season over the first season could be attributed to the cumulative effect of the addition of animal manure in the second cropping season [31] and the amount of rainfall received in the second cropping season which was higher than the rainfall received in the first cropping season (Table 3). These results are in agreement with many findings of several researchers who revealed that organic manure at various growing stages increases crop growth and yield [28,33,63]. Akparobi [31] recorded the highest plant height (123 cm) and dry matter (0.99 kg plant −1 ) of amaranthus cruentus (red amaranth) under 35 t ha −1 of poultry manure as compared to 0, 15 and 25 t ha −1 .…”
Section: Effect Of Tillage and Manure Rate On Aboveground Biomass Lai...supporting
confidence: 92%
See 1 more Smart Citation